Réponses

2014-09-07T14:43:34+02:00
E = (5x+2)(4x-3) + (5x+2)(6x+4)

le facteur commun est 5x+2

E = (5x+2)(4x-3+6x+4)
E = (5x+2)(10x+1)


F = (7x-1)(4x+2) + 5(4x+2)

Le facteur commun est 4x+2

F = (4x+2)(7x-1+5)
F = (4x+2)(7x+4)
merci d'avoir pris le temp de repondre a l,exercice
de rien ;)
Meilleure réponse !
  • Utilisateur Brainly
2014-09-07T15:00:00+02:00
(5x + 2)(4x - 3) + (5x + 2)(6x + 4)
= (5x + 2)(4x - 3 + 6x + 4)
= (5x + 2)(10x + 1)

(7x - 1)(4x + 2) + 5(4x + 2)
= (4x + 2)(7x - 1 + 5)
= (4x + 2)(7x + 4)